Utilizing the Literacycloud.org Website in Reading Comprehension: Students’ Perceptions - Lutfi Putri Khairani; Siti Ismahani (Universitas Islam Ahmad Dahlan (UIAD), 2026)
This study explores students’ perceptions of utilizing the LiteracyCloud.org website in reading comprehension activities among Tsanawiyah students. A descriptive qualitative approach was employed involving 29 participants selected using a purposive sampling technique. Questionnaires were distributed to all students, while data were also collected through classroom observations, semi-structured interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that students generally hold positive perceptions toward the use of LiteracyCloud.org in reading comprehension activities. Most students reported favorable responses regarding perceived ease of use (86.21%), attractiveness (89.66%), usefulness (82.76%), learning comfort (86.21%), and satisfaction (86.21%). In addition, the platform supported students’ reading-related activities, including reading frequency (82.76%), motivation (79.31%), engagement (75.86%), comprehension (79.31%), and overall reading interest (79.31%). The findings indicate that the utilization of LiteracyCloud.org provides an interactive and engaging reading environment that supports students’ reading comprehension. Students’ positive perceptions toward the platform also contribute to their active participation and engagement in literacy activities. This study implies that integrating digital reading platforms such as LiteracyCloud.org into classroom instruction can support students’ reading comprehension development and create more meaningful reading comprehension in the digital era.